2009
DOI: 10.1089/end.2008.0507
|View full text |Cite
|
Sign up to set email alerts
|

Combined Removal of Stones with Resection of Concurrent Pathologic Ureter May Be a Preferred Treatment for Impacted Ureteral Stones with Stricture Lesions

Abstract: Chronically impacted stones are frequently associated with ureteral polyp or stricture lesions. Our results reveal that combined removal of stones with resection of the pathologic ureter may achieve better long-term outcomes for patients with impacted stones with stricture lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…After the procedure, an indwelling 5‐F JJ stent was placed in each patient and remained in situ for 3–6 weeks after surgery, until patients were stone‐free on follow‐up radiography. Image protocols were plain abdominal film of kidney, ureter and bladder and US, which was performed to confirm SRH formation and to verify stone passage [6].…”
Section: Methodsmentioning
confidence: 99%
“…After the procedure, an indwelling 5‐F JJ stent was placed in each patient and remained in situ for 3–6 weeks after surgery, until patients were stone‐free on follow‐up radiography. Image protocols were plain abdominal film of kidney, ureter and bladder and US, which was performed to confirm SRH formation and to verify stone passage [6].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that concurrent ureteral lesion is related to a significant longer impaction, which makes a spontaneous passage difficult. 3,12,19 Based on the results of this study, secondary signs on UHCT were able to predict the presence of concurrent ureteral lesion. Therefore, even in small distal ureteral stones <5 mm, if secondary signs such as high degree of the tissue rim sign and hydronephrosis are identified on UHCT, early intervention seems to be better than prolonged conservative management to avoid the potential risk of urinary tract infection or deterioration of renal function.…”
Section: Discussionmentioning
confidence: 74%
“…Compared with the ureteroureterostomy group, a higher incidence of ureteral stricture was observed in the URL group (26.2% vs. 4.0%; p = 0.019). This result showed that the removal of the pathologic ureter with a polyp or stricture lesion might reduce the long-term risk of ureteral stricture for patients with impacted stones [15] .…”
Section: Risk Factorsmentioning
confidence: 80%
“…Xi et al. [15] compared the outcomes of URL and ureteroureterostomy for patients with impacted ureteral stones. Compared with the ureteroureterostomy group, a higher incidence of ureteral stricture was observed in the URL group (26.2% vs. 4.0%; p = 0.019).…”
Section: Risk Factorsmentioning
confidence: 99%